Trajectories of resilience to acute malnutrition in the Kenyan drylands - Bhavnani, Ravi; Schlager, Nina; Reul, Mirko; Donnay, Karsten (Frontiers in Sustainable Food Systems, 2023)
Insight into the resilience of local food systems-variability driven by climate, conflict, and food price shocks-is critical for the treatment and prevention of child acute malnutrition. We use latent class mixed modeling to develop a measure of resilience that is outcome-based, sensitive to specific shocks and stressors, and captures the enduring effects of how frequently and severely children face the risk of acute malnutrition. Harnessing a high-resolution longitudinal dataset with anthropometric information on 5,597 Kenyan households for the 2016-20 period, we identify resilience trajectories for 141 wards across Kenya. These trajectories-characterized by variation in the duration and severity of episodes of acute malnutrition-are associated with differential risk:(1) some 57% of wards exhibit an increasing trajectory-high household risk despite growing resilience; (2) 39% exhibit chronic characteristics-showing no real signs of recovery after an episode of crisis; (3) 3% exhibit robust characteristics-low variability with low-levels of individual household risk; whereas (4) 1% show a steady decrease in resilience-associated with high levels household risk. Our findings highlight the importance of measuring resilience at the ward-level in order to better understand variation in the nutritional status of rural households.